The influence of politics on the governance of an entrepreneurial ecosystem in a developing country: a generative institutional discourse approach - Kromidha, Endrit; Altinay, Levent; Arici, Hasan Evrim (Informa UK Limited, 2024)
Entrepreneurship is often about the individual drive for innovation and the exploitation of opportunities; however, in an increasingly connected world, entrepreneurial ecosystems have gained considerable research interest. In many developed countries, entrepreneurial ecosystems emerge from organic collaborations between businesses and investors, with little political involvement. However, in a post-communist country like Kazakhstan, different stakeholders have diverse expectations, leading to tensions among them. In this study, we took a qualitative approach and drew from discursive institutionalism theory in entrepreneurship research in order to understand the influence of politics on the governance of an entrepreneurial ecosystem. Our findings reveal tensions between collective aspirations and individual goals, generating multiple institutional logics. The generative institutional discourse that is brought about by politics, their influence on governance, and facilitating factors is a mechanism that helps to turn such tensions into policies and collective action. To gain a better understanding of the influence of politics on the governance of entrepreneurial ecosystems, we propose a generative institutional discourse model.
Keywords: 8. Economic growth; 1. No poverty; 16. Peace & justice